Seasonal variation of C-reactive protein and atherosclerotic cardiovascular events in hemodialysis patients - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2010)
Background: Atherosclerotic cardiovascular diseases (ACVD) is the most common cause of mortality in hemodialysis (HD) patients and the annual mortality in this population is about 10%. Inflammation is one of the most important predictor of ACVD morbidity and mortality in these patients. Recent studies demonstrated that levels of inflammatory markers and ACVD mortality vary seasonally in healthy population and in high-cardiac-risk populations. In this retrospective analysis, we aimed to determine seasonal variation of inflammation and ACVD morbidity and mortality in HD patients. Material and methods: Data were retrieved retrospectively for 1 year. Patients with acute or chronic infections or inflammatory conditions were excluded from the analysis. Laboratory data and ACVD-related events were retrieved from patients' files and these data were classified into seasonal periods. Results: Sixty-two patients were included in the final analysis. During follow-up period, geometric means of serum hsCRP levels were similar in all of the seasonal periods (4.17, 4.17, 4.57, and 4.17 mg/L in winter, spring, summer, and autumn, respectively). Means of hsCRP values were significantly higher in patients with active-ACVD compared to patients with no-ACVD in winter (3.38 vs. 13.18 mg/L, p < 0.05) and in autumn (3.63 vs. 23.4 mg/L, p < 0.05). There were 5 mortality and 7 morbidity and 12 combined morbidity and mortality related to ACVD and the distribution of these events were similar in all of the seasonal periods. Conclusions: Our study demonstrates that hsCRP levels and ACVD events do not show seasonal variation in HD patients.
Keywords: inflammation; mortality; seasonal variation; hemodialysis; ACUTE MYOCARDIAL-INFARCTION; CARDIAC-DISEASE; RISK-FACTORS; FACTOR-VII; INFLAMMATION; FIBRINOGEN; MORTALITY; MARKERS; CORONARY; ASSOCIATION